In silico B-cell and T-cell epitope-based vaccine designing against Chikungunya virus - Anushe, Sheikh (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of B.Sc in Microbiology, 2018.